1892 R.I. Pub. Laws 14 - (:unkn) unknown (My University, 1892)
An Act In Amendment Of Chapter 92 Of The Public Statutes, Entitled “Of Firearms And Fireworks, §§ 1, 3: Every person who shall discharge any rifle, gun, musket, blunderbuss, fowling piece, pistol, air gun, spring gun, or other contrivance arranged to discharge shot, bullets, arrows, darts, or other missiles in or across any road, street square, or lane shall be fined not less than three dollars nor more than twenty dollars.
Keywords: DISCHARGE